HEAVY CONCENTRATE GOLD ASSOCIATIONS IN THE BASIN OF THE KUKULKINDZHA CREEK (OKHOTSK REGION OF THE KHABAROVSK KRAI) - A.Ya. Nefedova; I.K. Kotova; М.А. Pavlova; D.I. Smirnov; D.А. Guskov; S.V. Petrov (Минералогия, 2024)
This article highlights an insufficiently studied issue of a primary source of placer gold in alluvium of the basin of the Kukulkindzha Creek (Okhotsk region, Khabarovsk krai) be means of the analysis of mineralogical and geochemical features of samples. This study provides information on mineral composition of heavy concentrates and morphological characteristics and chemical composition of native gold. Native gold with lumpy morphology is dominant in heavy concentrates. The fineness of native gold varies from very low (530–689 ‰) to medium (885 ‰); native gold contains only Ag and is characterized by high-fineness rims. The minerals of the garnet group with dominant grossular-andradite composition and the minerals of the pyroxene group (diopside–hedenbergite series characteristic of contact metamorphosed rocks) are always found in heavy concentrates. Three stable mineral assemblages of native gold are identified on the basis of statistical analysis of geochemical and mineralogical data. The first assemblage is related to the presence of heavy fraction minerals in heavy concentrates, which were sourced from the entire studied area. The second assemblage mainly consists of accessory minerals of Late Cretaceous subalkali granites, which are most widespread within the studied area, and the third assemblage contains skarn minerals. A primary source is most likely related to skarns, which is evident from specific features of native gold, as well as its presence in assemblage with Ca garnets of the grossular–andradite series and pyroxenes of the diopside-hedenbergite series. The samples with the highest amount of native gold in heavy concentrates are associated with skarn source.